Eosinophilic esophagitis and esophageal microbiota - Zhang, Xiaohan; Zhang, Nana; Wang, Zikai (Frontiers in Cellular and Infection Microbiology, 2023)
Eosinophilic esophagitis (EoE) is an antigen-mediated chronic inflammatory disease of the esophagus, the prevalence of which has steadily increased in recent years. The pathogenesis of EoE is not yet well-defined; however, recent studies have demonstrated that the esophageal microbiota is an essential regulator of physiological and pathological processes of EoE. Currently, research on EoE and microbiota is an emerging field of study that is receiving increasing attention. Here, we review existing EoE-related esophageal microbiota studies to explore the potential mechanisms underlying esophageal microbiota-mediated EoE. The esophageal microbiome is altered in patients with EoE.Although α diversity is usually not significantly different, an increase in Haemophilus and a decrease in Firmicutes were observed in EoE patients. The role of microbiota in initiating and perpetuating inflammation is not fully understood. Current evidence suggests that the penetration of microbiota leads to the activation of epithelial cells as well as innate and adaptive immune cells, with the subsequent release of cytokines, leading to immune responses and inflammation. The involvement of toll-like receptors in EoE also supports the potential role of the microbiota in the progression of this disease. While EoE-induced inflammation can also lead to alterations in the local microbiome.Moreover, dietary modifications, proton pump inhibitors, and corticosteroids can modulate the esophageal microbiota; however, definitive conclusions about the alterations of microbes after treatment cannot be drawn. These findings provide promising avenues for future studies.